Analisis Penilaian Kesehatan Bank Menggunakan Metode Risk Profile, Earning dan Capital Pada BPRS - Raihani, Hulfa (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
The aim of this research to was find out the health level Islamic Rural Banks in West Sumatra Province for the 2014-2018 period using the Risk Profile, Earning, and Capital methods. This research used a quantitative approach that was supported by the use of descriptive statistical analysis. The results show that this study can be concluded that during 2014-2018 based on several financial ratios that exist in the RGEC method, namely Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Return on Asset (ROA), Return on Equity (ROE), Beban Operasional Pendapatan Operasiona (BOPO) and Capital Adequacy Ratio (CAR) at Islamic Rural Banks , which consists of PT BPRS Ampek Angkek Canduang, PT BPRS Carana Kiat Andalas, and PT BPRS Haji Miskin as a whole are ranked less healthy (PK-4), with a composite value of 56.66%,